Geochemical insight during archaeological geophysical exploration through in situ X‐ray fluorescence spectrometry. Issue 4 (15th June 2017) - Booth, Adam D.; Vandeginste, Veerle; Pike, Dominic; Abbey, Russell; Clark, Roger A.; Green, Chris M.; Howland, Nathan
Abstract: Geophysical techniques are widely applied in archaeological exploration, providing rapid and non‐invasive site appraisal. Geochemical analyses contribute significantly in archaeometry, but conventional laboratory apparatus requires that samples are removed from their in situ context. Recent advances in field‐portable apparatus facilitate in situ geochemical analysis, and this apparatus is deployed in this paper alongside conventional geophysical analysis to characterize the archaeological prospectivity of a site. The target is subsurface debris at the crash site of a World War II Mosquito aircraft. A 100 m long transect of magnetic, electromagnetic (EM) and in situ X‐ray fluorescence (XRF) measurements was acquired in November 2014, with soil samples also collected for laboratory validation. A subset of XRF measurements was repeated in August 2015 alongside a targeted grid, 900 m 2 in area, of magnetic gradiometry profiles. Built chiefly from wood, the Mosquito responds weakly in magnetic and EM data; magnetic gradient anomalies of ±10 nT/m are instead attributed to thermoremanence in a burnt layer at 0.2–0.4 m depth, produced by the impact fire following the crash. XRF spectrometry reveals co‐located enrichments in copper (Cu) and zinc (Zn) ions (400% and 200%, respectively, above background). These metals are alloyed into brass, present in abundance in the ammunition on board the Mosquito . Records from the in situ XRF sampling compare well with laboratory validated data, although a bespoke calibration for the local soil type would improve the reliability of absolute geochemical concentrations. XRF responses vary significantly with ground conditions: the November 2014 acquisition was performed soon after ploughing at the site, potentially providing a fresh charge of metallic contaminants to the ground surface. Where the chemistry of a target is anomalous with respect to host soil and a source‐to‐surface transport mechanism is present, in situ XRF analysis offers improved understanding of a target compared to geophysical interpretation alone.